Evaluation of antioxidant, antibacterial and anticancer activities of ganoderma lucidum extracts - Nurul Izzati, Azahar; Swan, Sia Yiik; Nur Syahirah, Mohd Razi; Zhen, Wan Yan; Mohd Azmir, Arifin (Elsevier Ltd, 2023)
G. lucidum is an oriental fungus loaded with antioxidant, antimicrobial and anticancer properties. G. lucidum extracts obtained by using soxhlet and Ultrasonic-Assisted Extraction (UAE). The antioxidant activity determined by DPPH assay resulting in IC50 value of extract for soxhlet water 372.21μg/mL followed by soxhlet ethanol 431.00μg/mL, UAE ethanol 541μg/mL and UAE water 560.90μg/mL shown weak antioxidant properties. Well plate diffusion used for antimicrobial activity test against E. coli and S. aureus. The UAE water extract shown highest antibacterial activity against S. aureus (20-23) mm followed by soxhlet water extract (6-13) mm. The ethanol extract for both soxhlet and UAE are (5-13) mm and (4-14) mm respectively. G. lucidum extract exhibited zero inhibition zone against E. coli due to presence of barrier membrane. CCK-8 used to test anticancer activity against MCF-7 cells. The IC50 values of soxhlet ethanolic extract is 4.797 μg/mL followed by UAE ethanolic extract 5.291 μg/mL, soxhlet water extract 7.196 μg/mL and UAE water extracts 9.455 μg/mL. The lower IC50 value indicated that the extracts inhibited cell viability of MCF-7.